First-time report on compound isolation from two Colocasia species: vegetable-derived bioactive metabolites and their medicinal potential - Alam, Safaet; Richi, Fahmida Tasnim; Emon, Nazim Uddin; Chowdhury, Abu Asad; Hasan, Choudhury Mahmood; Haque, Mohammad Rashedul (Frontiers in Pharmacology, 2024)
Background Colocasia affinis Schott and Colocasia gigantea Hook.f. are two commonly found vegetable species of the genus Colocasia, found mainly in the Asian region. Objectives The objective of this study was to isolate bioactive phytochemicals from C. affinis and C. gigantea and elucidate their structure employing the NMR technique followed by bioactivity evaluation. Methodology Column chromatography was utilized to isolate phytochemicals, followed by NMR analysis for characterization. An in vivo analgesic test was performed through an acetic acid-induced writhing test, an anti-inflammatory test was performed through a formalin-induced licking test, and an antidiarrheal test was performed through a castor oil-induced diarrhea model. The in vitro antimicrobial test was executed through the disc diffusion method. Computer-aided simulation was also implemented to validate the wet laboratory results. Results Six compounds from C. affinis and C. gigantea were isolated and characterized from the dichloromethane (DCM)-soluble fractions of the methanolic extracts of these two species. Three of the compounds were from C. gigantea and proposed as penduletin (C1), a mixture of α-amyrin (C2a), β-amyrin (C2b), and monoglyceride of stearic acid (C3), while the remaining three compounds were from C. affinis and proposed as penduletin (C4) (which was also isolated from C. gigantea), 7,8-(3″,3″-dimethyl-pyrano)-4′-hydroxy flavonol (C5), and lastly a mixture of 7,8-(3″,3″-dimethyl-pyrano)-4′-hydroxy flavonol (C5) and 4′,7,8-trihydroxy flavonol (C6). These compounds showed promising zones of inhibition against Gram-positive and Gram-negative bacteria and fungi. In the antidiarrheal test, C5 demonstrated the highest reduction in castor oil-induced diarrhea (44.44%) at a dose of 20 mg/kg compared to loperamide’s 77.78% reduction. However, the analgesic assessment showed a noteworthy inhibition of acetic acid-induced writhing by C1/C4 and C2 (56.52%) at a dose of 20 mg/kg compared to the 76.09% by diclofenac sodium. In comparison, C2 showed pronounced anti-inflammatory action by 68.15% and 52.06% reduction, respectively, in the early and later phases compared to the ibuprofen’s outcomes of 73.54% and 74.68%. Plausible targets such as dihydrofolate reductase (DHFR) for antimicrobial, kappa opioid receptor (KOR) for antidiarrheal, and cyclooxygenase 2 (COX-2) for anti-inflammatory and analgesic activities showed a noteworthy binding affinity with isolated compounds, and ADME/T studies displayed these phytochemicals’ drug-likeness profiles. Conclusion To the best of our knowledge, this is the first report on compound isolation from these plants, which demands further extensive research for more absolute findings.